Cooling by Natural Ventilation - Upadhyay, Urvi Paras; Lalwani, Vijay Kishanchand (IJRDO - Journal of Mechanical And Civil Engineering, 2018)
Naturally, ventilated and lighted buildings have a key role to play in mitigating climate change. Nowadays no one concentrates in the functional design of building like natural ventilation and lighting. In some highly populated areas does not gather any natural ventilation and lightings inside the buildings. The main study of the project is how to get natural energy gains into the buildings. Ventilation and lighting plays a vital role not only in buildings but also psychology and comfort level of occupants using the building. Building without ventilation and lighting will be a bad design and also called as sick building. Natural lighting and ventilation is mandatory part of today’s design to save energy. It can also be called as heart of a building design. The main aim of our study is to give a conclusion for gathering natural ventilation and lighting inside the buildings. We choose one residential building in the populated area, analysed the problems and provide solutions to get natural ventilation and lights.